Consumer Sentiment During the COVID-19 Pandemic: The Role of Others' Beliefs - Dzung Bui; Lena Dräger; Bernd Hayo; Giang Nghiem (Philipps-University Marburg, School of Business and Economics, 2020)
This paper investigates the direct and indirect effects of others' beliefs on respondents' own beliefs and consumer sentiment. Conducting consumer surveys with randomized control trials (RCTs) in Thailand and Vietnam during the COVID-19 pandemic, we implement two information treatments. Both treatments contain cross-country information about others' beliefs about the appropriateness of the government's or the general public's reaction to the pandemic. The first treatment is asymmetric across our sample countries, as it shows opposite appropriateness ratings of the governments' reaction in Vietnam and Thailand, whereas the second treatment is rather symmetric. We find that the information treatments affect consumer sentiment only in Vietnam, where the sign of the effect suggests that the treatments are viewed as positive news. Moreover, consumer sentiment in Vietnam is strongly affected by both treatments when the information goes against respondents' prior beliefs.
Keywords: E21; E37; E71; D84; D83; 330; Consumer sentiment; COVID-19; randomized control trial (RCT); survey experiment; second-order beliefs; belief updating; government trust; macroeconomic expectations; Thailand; Vietnam